Molluscicidal and cercaricidal effects of Persicaria senegalensis on Radix natalensis snails and their echinostome-shed cercariae in South Africa. Issue 1 (2nd January 2023) - Mathole, MC; King, PH
Abstract : Persicaria senegalensis is an aquatic plant of the Family Polygonaceae with apparent molluscicidal properties. The research evaluated the molluscicidal effect of P. senegalensis on the freshwater snail Radix natalensis, and its echinostome-shed cercariae. Various compounds from Persicaria senegalensis were extracted and qualitatively analysed. Radix natalensis and the cercariae were exposed to different extract concentrations of P. senegalensis and tested for a period of 24 and 3.5 hours, respectively. Glycosides, saponins, tannins and phenols were found to be present in the leaf, flower and stem extracts. The roots only contained saponins, with traces of tannins and phenols. Terpenoids were absent in the plant. The LC50 values of P. senegalensis extracts against R. natalensis were determined at 18.20 ± 14.78, 30.90 ± 31.25, 42.66 ± 55.67 and 77.62 ± 132.31 for leaves, flowers, stems, and roots respectively. For the cercaricidal activities of leaf, flower, stem and root extracts, the LC50 values against R. natalensis -shed cercariae were 20.89 ± 8.91, 30.90 ± 22.10, 42.66 ± 40.94 and 77.62 ± 93.62, respectively. The mortality rate of tested organisms increased with increased concentrations. It is concluded that extracts of P. senegalensis have molluscicidal and cercaricidal properties; and, therefore, has potential as an alternative biological control agent for freshwater snails, their cercariae and, subsequently, other snail-transmitted parasitic diseases.